The Migration In Metropolitans And The Use Of Public Areas Of The Different Cultures In Istanbul - Yalçın, Döndü Ferhan; Melikoğlu Eke, Armağan Seçil (My University, 2012)
Urbanization movements have started to expand to metropolitan urbanism along with the industrial revolution and irrigated agricultural revolution that triggered the migration from rural to urban and the existing investments that turn to metropolitan cities in Turkey. Istanbul has been the most affected city by this. Istanbul isn’t only the industrial city of Turkey, at the same time it is a coastal city that provide the movement of the currency market, a city of culture and a city of education. This multi-layered city began to evolve into a multi-identity metropolis with different typological migrations. Having a wide variety of identities were reflected the city's public areas, the tracks of different cultures can be read as displaying significant variations in public places. Traces of people with different cultures and different social fields, has become visible on the streets of the city. This versatility has started to draw its own border. Working with this idea the aim of the study is to determine what kind of changes occurred the multi-identity, cultural structure with migrations in Istanbul on the tracks of the public areas of the metropolitan city and how this effects have changed the perspective of people living in public spaces of the city. The study will be made in The Historical Peninsula of Istanbul. Within the scope of this study the method is based on readings of the selected street and building facades. This selected building facades and streets are analyzed with visual tables.